Low variability of the Atlantic Meridional Overturning Circulation throughout the Holocene - Gerber, Lukas; Lippold, Jörg; Süfke, Finn; Valk, Ole; Testorf, Pierre; Ehnis, Manuel; Tautenhahn, Saskia; Max, Lars; Chiessi, Cristiano M.; Regelous, Marcel; Szidat, Sönke; Friedrich, Oliver; et al. (Nature Communications, 2025)
Earth system models and paleo-reconstructions indicate that shifts in Atlantic Meridional Overturning Circulation (AMOC) strength profoundly impact global climate. While the last glacial termination experienced large AMOC variations, evidence of AMOC changes during the Holocene are poorly constrained. Here we present a Holocene AMOC reconstruction by quantifying mean bottom water advection strength in the deep North Atlantic. For this, we estimated volumetric flow rates from sedimentary 231Pa/230Th records with millennial resolution using the Bern3D model. We found that while during the Early Holocene the AMOC recovered from its weak deglacial state, it experienced a weakening between 9.2 to 8 ka BP, coinciding with North Atlantic meltwater pulses. From 6.5 ka BP onward, the AMOC strength stabilized, reaching its pre-industrial state around ~18 Sv. Hence, according to future projections, anthropogenic climate change may result in an AMOC slowdown unprecedented for most of the ongoing Holocene interglacial.
Gesehen am 12.12.2025